Trends and spatial variation in water and land footprints of meat and milk production systems in Kenya - Bosire, Caroline K.; Ogutu, Joseph O.; Said, Mohammed Yahya; Krol, M.S.; Leeuw, Jan de; Hoekstra, A.Y. (Elsevier, 2015)
Global consumption of livestock products is increasing steadily due to human population growth, poverty reduction and dietary changes raising the demand for already scarce freshwater and land resources. Here, we analyze the changes associated with direct and indirect use of freshwater and land for meat and milk production in three production systems in Kenya between the 1980s and 2000s. We use two resource use indicators, the water footprint (m3/year) and land footprint (ha), to assess changes in freshwater and land use for cattle, goats, sheep and camels in arid, semi-arid and humid production systems. We estimate actual water and land use using Kenya-wide data for yields, feed composition and feed conversion efficiencies. Our results show that the amounts of freshwater and land resources used for production are determined mainly by production volumes and feed conversion efficiencies. Total water and land footprints of milk production increased for goats, sheep and camels but decreased by half for cattle in arid and semi-arid production systems, in correspondence with similar changes in the total numbers of each livestock species. Green water and grazing land footprints dominated in all production systems due to the predominance of indirect use of water to support forage production. The per unit meat footprint for cattle increased significantly between the 1980s and 2000s in all production systems, due to adverse trends in feed conversion efficiency, while changes in the water and land footprints of other animal products were small, due to modest changes in all influencing factors. In contrast, national average footprints per unit of beef and milk show a modest decrease due to a relative shift of production to the more resource-efficient humid production system. Given the potential increase in demand for livestock products and limited freshwater and land availability, feed conversion efficiencies should be improved by rehabilitating degraded rangelands, adopting improved breeds and using appropriate feed composition.